The surface passivation mechanism of graphene oxide for crystalline silicon - Vaqueiro-Contreras, M; Walton, AS; Bartlam, C; Byrne, C; Bonilla, RS; Markevich, VP; Halsall, MP; Vijayaraghavan, A; Peaker, AR (IEEE, 2020)
We have recently demonstrated that low surface recombination velocities on Si crystals are achievable from room temperature graphene oxide (GO) deposition. Intrinsic properties of this material make it an appealing candidate for surface passivation in solar cells. There is, however, very little literature on the passivation mechanisms of GO and further understanding is required. In this work we have thus studied GO/SiO2/Si interface interactions by X-ray photoelectron spectroscopy (XPS). From our results we have confirmed that the passivation achieved by GO coatings do not result from chemical changes at the surfaces as has been previously suggested. In addition, close analysis of the spectra of GO coated silicon sample shows the elemental Si 2p peak is split into two doublets. We identify the appearance of this extra doublet to be the result of surface charging, and thus attribute the spectral change to formation of a depletion region at the silicon surface induced by GO's negative charge. Results in here presented may thus signify a significant step forward in the understanding of charged 2D materials passivation mechanisms and its use in advanced solar cell structures.